Internal Medicine Point-of-Care Ultrasound Curriculum: Consensus Recommendations from the Canadian Internal Medicine Ultrasound (CIMUS) Group - Ma, Irene W. Y. (J Gen Intern Med, 2017)
Bedside point-of-care ultrasound (POCUS) is increasingly used to assess medical patients. At present, no consensus exists for what POCUS curriculum is appropriate for internal medicine residency training programs. This document details the consensus-based recommendations by the Canadian Internal Medicine Ultrasound (CIMUS) group, comprising 39 members, representing 14 institutions across Canada. Guiding principles for selecting curricular content were determined a priori. Consensus was defined as agreement by at least 80% of the members on POCUS applications deemed appropriate for teaching and assessment of trainees in the core (internal medicine postgraduate years [PGY] 1–3) and expanded (general internal medicine PGY 4–5) training programs. We recommend four POCUS applications for the core PGY 1–3 curriculum (inferior vena cava, lung B lines, pleural effusion, and abdominal free fluid) and three ultrasound-guided procedures (central venous catheterization, thoracentesis, and paracentesis). For the expanded PGY 4–5 curriculum, we recommend an additional seven applications (internal jugular vein, lung consolidation, pneumothorax, knee effusion, gross left ventricular systolic function, pericardial effusion, and right ventricular strain) and four ultrasound-guided procedures (knee arthrocentesis, arterial line insertion, arterial blood gas sampling, and peripheral venous catheterization). These recommendations will provide a framework for training programs at a national level.